The efficacy of virtual reality in adults during puncture biopsy: A systematic review and meta-analysis of randomized controlled trials - Xueling Qiu; Wei Gong; Cui Li; Xiaochen Jiang; Weifeng Wang; Fan Sun; Chenxi Sun; Wenjuan Cao; Lu Tang (PLoS ONE, 2025)
Background Virtual reality, as a nascent technology, possesses the potential to enhance patient comfort by mitigating pain and anxiety during medical procedures. This study aimed to evaluate the efficacy of virtual reality intervention in managing pain for adults undergoing puncture biopsy procedures. Methods From the outset of the development of databases until October 8, 2024, a comprehensive search of the published literature was performed across eight electronic databases. The collected data was consolidated and subjected to meta-analysis by using RevMan 5.4. The quality of the inclusion of randomized controlled trials in terms of methodological quality was assessed by the Cochrane Risk of Bias Assessment Tool. Additionally, strength and certainty of the evidence was assessed by the GRADE system. Results The study was conducted on data from a sample of 445 patients from six randomized controlled trials. The pooled analysis revealed that the virtual reality group demonstrated an analgesic effect (MD = −1.61, 95% CI: −2.54 to −0.68; p = 0.0007; I2 = 90%). Moreover, the virtual reality intervention was found to reduce patient anxiety during puncture biopsy procedures (MD = −9.49, 95% CI −14.47 to −4.50; p = 0.0002; I2 = 88%). In addition, three studies that could not be included in the meta-analysis also reported a positive impact of increasing patient satisfaction with the operation. Conclusions Virtual reality can be used as an analgesic method in adult puncture biopsies and as a reliable alternative therapy in clinical settings, providing a valuable non-pharmacologic approach to pain management. Nevertheless, the level of evidence is relatively low, thus further high-quality studies are required to substantiate our conclusion. Systematic review registration PROSPERO database, CRD4202459303.